Learning shapes and colours using JomLearn & Play Application for Children / Madiawati Musa … [et al.] - Musa, Madiawati; Mazlan, Azlimi; Engku Mohamed Fathilullah, Engku Nuraisha; Amir, Aimi Liyana; Zulkifli, Norlindamalia; Mohd Salleh, Nurhashikin (Faculty of Computer and Mathematical Sciences, 2022)
Learning shapes and colours are the basic cognitive development for children. Children learn best through sorting size, shapes, and colours. Nowadays, most of the application available mostly using English language. This study found that there are very limited applications using Malay language. The current existing application available found in Indonesia language. JomLearn & Play is the application focus on children to learn the basic shapes and colours using Malay language. The method used is ADDIE model consists of analysis, design, development, implementation, and evaluation. The JomLearn & Play application can help the children in early stage to learn about shapes and colours.